2018
DOI: 10.1055/s-0043-118348
|View full text |Cite
|
Sign up to set email alerts
|

High Dose of A Conjugated Linoleic Acid Mixture Increases Insulin Resistance in Rats Fed Either A Low Fat or A High Fat Diet

Abstract: Obesity and related diseases are becoming more prevalent. Conjugated linoleic acid (CLA) might be a useful coadjutant treatment helping to decrease fat mass. However, the precise impact of CLA is unclear because the decreased body fat mass is followed by an increase in insulin resistance. This study aimed to evaluate some of the consequences of a high dose of CLA in rats fed a normal low fat or a high fat diet for 30 days. Male Wistar rats were separated into 4 groups (each n = 10): Control group receiving 7% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
1
14
1
1
Order By: Relevance
“…On the other hand, commercial mixtures of RA and C 18:2 t10, c12 (i.e., CLAcontaining oils) were found to exert negative effects, such as impairment of both medium-and long-term spatial learning and memory in rats with brain lesions (12) or increased insulin resistance in male Wistar rats fed either high-or low-fat diets (13). The latter effect has also been observed in humans but, in general, seems to be associated with C 18:2 t10, c12 (14,15).…”
Section: Cla and Clna Bioactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, commercial mixtures of RA and C 18:2 t10, c12 (i.e., CLAcontaining oils) were found to exert negative effects, such as impairment of both medium-and long-term spatial learning and memory in rats with brain lesions (12) or increased insulin resistance in male Wistar rats fed either high-or low-fat diets (13). The latter effect has also been observed in humans but, in general, seems to be associated with C 18:2 t10, c12 (14,15).…”
Section: Cla and Clna Bioactivitymentioning
confidence: 99%
“…When assaying the quantitative and qualitative transfer of 13 C to CFA, a mixed microbial population from the rumen of a dairy cow was tested in batch cultures in the presence of [ 13 C]LNA (25). During the incubation time (48 h), both nonconjugated and conjugated 18:2 and 18:3 isomers were enriched with 13 C. Interestingly, for C 18:2 , six unknown isomers were reported, while for C 18:3 , there were 10 plus 2 conjugated forms listed. Formation of RA and isomers C 18:2 t10, c12 plus t9, t11; t9, c11; c9, c11; t11, t13; t8, t10; and c10, c12 was also observed.…”
Section: Cfa and Rumen Biohydrogenationmentioning
confidence: 99%
“…Feeding lactating mice with CLA can result in diminished mammary gland lipogenesis and reduced growth rate [18,19], but the exact metabolic and physiological changes involved remain unclear. More recently, Bezan (2018) demonstrated that feeding a high dose (3%) of CLA increases insulin resistance and exacerbates hepatic steatosis in male Wistar rats [20]. The intake of trans-fatty acids during lactation was also found to increase maternal lipids in the liver (Assumpção, 2004) and liver weight [21].…”
Section: Introductionmentioning
confidence: 99%
“…CLAs used in supplements originate from the processing of vegetable oils such as Safflower oil, and always include an equimolar mixture of c9,t11-CLA and t10,c-12-CLA. Most studies of CLAs have used a mixture of isomers, with c9,t11-CLA and t10,c-12-CLA the most abundant [20,22]. To explore this further, two experiments were performed in which mice were fed with a CLA mixture.…”
Section: Introductionmentioning
confidence: 99%
“…Ao contrário do que algumas pesquisas apontam (JACOB et al, 2013;SANTANA et al, 2014;LU et al, 2016;BUSSEROLLES et al, 2003), a dieta hiperlipídica e a restrição dietética de Mg não promoveram modificações no perfil lipídico e na concentração de citocinas inflamatórias no tecido adiposo. Porém, alguns estudos crônicos desenvolvidos com ratos Wistar alimentados com dietas hiperlipídicas relatam a ausência de inflamação e de alterações nos níveis de lipídios circulantes assim como o presente estudo (GZIELO et al, 2017;BEZAN et al, 2018). As diferenças nesses resultados podem decorrer das variações no teor de lipídios e no perfil de ácidos graxos da dieta, peso e idade dos animais utilizados e do tempo de estudo.…”
Section: Western-blotunclassified